Acesso a terapia medicamentosa na perspectiva de pacientes e profissionais de saúde - Josiane Moreira da Costa (2012)
Case study with qualitative approach based on comprehensive sociology aiming at understanding the access to medications during pre, intra and post-hospitalization, according to perspectives from users and health professionals of a teaching hospital. The studys scenario is a large general teaching hospital that is reference in trauma, urgent care and emergency located at the North of Belo Horizonte. Seven patients,nine companions and 14 health professionals, a total of 30 participants, were the subjects determined by data saturation. Data was collected through interviews based on a semi-structured script for each segment. The data was submitted to content analysis and organized in four categories: 1. From the medications that I take to the ones I dont know: in the hands of health professionals; subdivided into two subcategories Patients (in) activity vs. professional tecnicism and Hospital admission and discharge as landmarks to the caring transition; 2. (Des) continuity ofdrug therapy; 3. Information as medications access strategy; 4. Possibleaccessibility. Results show that medications earn greater or lesser projection in the patients care besides being one of the strategies of health care in hospitalization. Thus, access to drug therapy becomes heterogeneous and permeated by values, relations and subjectivities provoking feelings based on the understanding of the need to medication use, fear of re-hospitalization, non-availability of drug therapy in the Primary Health Care Unities and the users inability to buy medication. Despite programs which offer medication supplies, access to them in the pre and posthospitalization periods is fragile constituting one of the factors which strengthen the patients cyclical walk in the health care net. The access barriers regarding information present themselves as a complex issue which involves different work processes permeated by both patient-professional relationships and interprofessional ones. However, information is essential to guarantee access to drug therapy in order to avoid compromising medication supplies, prescription and availability. Early discharge preparation, referencing mechanisms implantation and patients subjectivities acknowledgement are some of the activities which contribute to guarantee medication access. As a conclusion, drug therapy is built from relationships and experiences lived by the actors involved and reveals itself an important technology to caring in every level of health care.